Cervical intraepithelial neoplasia. Issue 1 (January 1982) - Buckley, C H; Butler, E B; Fox, H
Abstract : The theoretical and practical reasons for replacing the terms "cervical dysplasia" and "cervical carcinoma in situ" by the single diagnostic entity of "cervical intraepithelial neoplasia" are reviewed and the advantages and drawbacks of this newer terminology discussed. The histological characteristics and cytological features of the various grades of cervical intraepithelial neoplasia are described and the differential diagnosis of this lesion is considered.